Is the cemetery dead? - Sloane, David Charles (The University Chicago Press, 2018)
"Is the Cemetery Dead? gets to the heart of the tragedy of death, chronicling how Americans are inventing new or adapting old traditions, burial places, and memorials. In illustrative prose, David Charles Sloane shows how people are taking control of their grief by bringing their relatives home to die, interring them in natural burial grounds, mourning them online, or memorializing them streetside with a shrine, ghost bike, or RIP mural. Today's mourners are increasingly breaking free of conventions to better embrace the person they want to remember. As Sloane shows, these changes threaten the future of the cemetery, causing cemeteries to seek to become more responsive institutions."--
Keywords: Cemeteries : United States; Funeral rites and ceremonies : United States; kuolema; rituaalit; hautausmaat; hautaustavat; surutyö; döden; ritualer; begravningsplatser; begravningsseder; sorgearbete; Yhdysvallat; Förenta staterna